Towards an international criminal procedure - Safferling, Christoph J.M. (Oxford University Press, 2003)
As international criminal law grows in importance and practical impact, long-standing questions of criminal procedure will need to be addressed: i.e. how do we reconcile continental-style and Anglo-American procedure? and how do we ensure that international norms of human rights are complied with. Through a systematic comparative and institutional study, this book provides an important guide to the future procedural order